SYARAH HADIS: MODEL DAN APLIKASI METODOLOGIS - Hariono, Duwi (IAIN Kediri, 2019)
H adi th is believed to be a guideline for life after the Qur?an, hence the various methods of understanding used must be appropriate so that the traditions can provide benefits for life. So far many criticisms have been directed at the classical hadith methodology of hadith because they are considered irrelevant to current needs. This criticism is not entirely true because after all the classical sharih method is still needed. At least as a reference for the new sharih hadith method so that he does not lose his footing. The effort that needs to be done is how to combine the old method with the new method so that the sharih of the hadith can produce a valid understanding. This article presents the development of Sharh Hadith since the 6th century until now using the historical-phenomenological approach. Furthermore, the Sharh Hadith methodology is also offered which applies the old methodology in the new direction accompanied by an explanation of the steps. Furthermore, also included a concrete example of the realization of the values of hadith in contemporary life. Thus the reader can find the meaning of syarh hadith in his real life.Keywords: Sharh, hadith, method, model